1995
DOI: 10.1007/bf02425152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracorporeal life support on cerebral blood flow, metabolism and electrophysiology in normothermic cats

Abstract: These data demonstrate that ECLS is associated with reduced cerebral oxygen delivery and may cause brain hypoxia despite normal blood pressure. This complication may contribute to the high incidence of neurological disturbances after prolonged ECLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Partial cardiopulmonary bypass (or partial cardiopulmonary support 20 ) is routinely used in clinical practice for extracorporeal life support in humans and sometimes also for experimental resuscitation. [21][22][23][24][25] Although intra-arterial administration of medication (eg, epinephrine) should be practiced with caution, the low doses used in the model can be further reduced when donor blood is used (such as in group 2), because the withdrawn donor blood and predetermined dose of medication need not be infused after ROSC is observed. As an experimental approach, our intraaortic blood infusion proves to be a very reliable method for remotely controlled resuscitation after prolonged cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Partial cardiopulmonary bypass (or partial cardiopulmonary support 20 ) is routinely used in clinical practice for extracorporeal life support in humans and sometimes also for experimental resuscitation. [21][22][23][24][25] Although intra-arterial administration of medication (eg, epinephrine) should be practiced with caution, the low doses used in the model can be further reduced when donor blood is used (such as in group 2), because the withdrawn donor blood and predetermined dose of medication need not be infused after ROSC is observed. As an experimental approach, our intraaortic blood infusion proves to be a very reliable method for remotely controlled resuscitation after prolonged cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…25 Early animal studies noted decreased cerebral oxygenation, altered cerebral autoregulation, and increased lactate despite normotension with extracorporeal life support. 20, 35 Barrett et al found acute neurological injury in 22% of pediatric patients undergoing ECPR from their retrospective review of the Extracorporeal Life Support Organization registry. They noted that lack of metabolic acidosis and underlying cardiac disease decreased the odds of neurological injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the test rig was constructed to produce very small virus aerosol droplets. The short duration of the exposure period was considered adequate because earlier studies had shown that filtration efficiency does not diminish for at least 24 hours [14], [15], [16], [17]. The filtration efficiency of mechanical filters actually tends to increase over time as the substances retained on the filter form a layer (“filter cake”), which gradually increases particle retention.…”
Section: Discussionmentioning
confidence: 99%